2012
DOI: 10.1007/s10689-012-9514-x
|View full text |Cite
|
Sign up to set email alerts
|

Families’ experience of oncogenetic counselling: accounts from a heterogeneous hereditary cancer risk population

Abstract: This paper reports the results of semi-structured family interviews conducted with a purposive sample of nine families (comprising 50 individuals) involved in cancer genetic counselling at a Portuguese public hospital. Qualitative analysis resulted in thematic categories illustrating: (1) how families go through cancer genetic counselling (eliciting risk awareness, the motivators, risk management, the psychosocial context of familial engagement in genetic counselling, and the familial pathways of cancer risk t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 68 publications
0
14
0
2
Order By: Relevance
“…The overall findings allow important and timely reflection on the provision of genetic counseling in Portugal and its effectiveness as the first generation of Portuguese genetic counselors is ready for integration in public healthcare services. The study adds to the growing body of research on psychosocial genetics at national level (Guimarães et al 2013;Leandro et al 2012;Mendes et al 2010;Mendes and Sousa 2012;Nunes et al 2012;Paneque et al 2012;Rodrigues et al 2012).…”
Section: Discussionmentioning
confidence: 85%
“…The overall findings allow important and timely reflection on the provision of genetic counseling in Portugal and its effectiveness as the first generation of Portuguese genetic counselors is ready for integration in public healthcare services. The study adds to the growing body of research on psychosocial genetics at national level (Guimarães et al 2013;Leandro et al 2012;Mendes et al 2010;Mendes and Sousa 2012;Nunes et al 2012;Paneque et al 2012;Rodrigues et al 2012).…”
Section: Discussionmentioning
confidence: 85%
“…Among 71 families with hereditary colorectal cancer, baseline hope has been associated with reduced distress (Ho, Ho, Bonanno, Chu, & Chan, 2010). Members of families with known genetic susceptibility to cancer have reported that baseline spirituality and adoption of optimism and mechanisms of social support encourage greater self-care and, ultimately, enable inner strength for individuals and their families (Mendes & Sousa, 2012). …”
Section: Resultsmentioning
confidence: 99%
“…O acesso à história médica da família é importante na avaliação do risco genético individual. Os familiares mais velhos têm sido descritos como "guardiões da história médica da família" pelo conhecimento privilegiado de circunstâncias de saúde de antepassados aos quais não é possível aceder (porque já morreram ou estão muito incapacitados) 12 .…”
Section: Introductionunclassified